2021
DOI: 10.1590/1678-4162-12111
|View full text |Cite
|
Sign up to set email alerts
|

Grass pollen sensitization in dogs in Paraná, Brazil: comparison between percutaneous and intradermal testing

Abstract: Canine atopic dermatitis is an inflammatory, genetic, pruritic and chronic dermatosis that affects between 10 and 30% of dogs and one of the most important allergens is grass pollen. The objective of this study was to evaluate the sensitization to grass pollen allergens in dogs with canine atopic dermatitis and to compare intradermal skin test (IDT) with percutaneous test (PT). For this study, ten healthy dogs and 39 dogs with atopic dermatitis were tested. Dogs were submitted to IDT and PT for Lolium multiflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Trees, weeds, and grass also contribute to sensitization [34]. Our findings (Figure -7) revealed that oak (34.6%), white ash (21.6%), maple leaf sycamore (18.2), sheep's sorrel (25.0%), mugwort (18.0%), Bermuda grass (15.7%), and common weed (14.2%) are the major allergens detected.…”
Section: Discussionmentioning
confidence: 75%
“…Trees, weeds, and grass also contribute to sensitization [34]. Our findings (Figure -7) revealed that oak (34.6%), white ash (21.6%), maple leaf sycamore (18.2), sheep's sorrel (25.0%), mugwort (18.0%), Bermuda grass (15.7%), and common weed (14.2%) are the major allergens detected.…”
Section: Discussionmentioning
confidence: 75%
“…Para protocolos científicos, recomenda-se o uso de quadruplicata (SOLDERA et al, 2015). Cerdeiro et al (2021) observaram que o teste de puntura foi mais eficaz na identificação da sensibilização do pólen de gramíneas em cães com dermatite atópica do que no teste intradérmico da pele. A sensibilização para o pólen de gramíneas ocorreu em cerca de um quarto dos indivíduos e as mais comuns foram a Cynodon dactylon e a Lolium multiflorum.…”
Section: Discussionunclassified
“…O principal sinal demonstrado na DAC é o prurido em áreas sem lesão visível, que leva a lesões cutâneas causadas pelo traumatismo autoinduzido e ao espessamento da camada córnea (hiperqueratose) por conta da fricção, infecção e processo inflamatório crônico. As áreas mais comumente acometidas são os espaços interdigitais, face, região periocular, região inguinal, axilas, virilhas e os pavilhões auriculares (CERDEIRO et al, 2021).…”
Section: Lesõesunclassified
See 1 more Smart Citation
“…However, in recent years there has been increasing investigation into use of the prick test (PT). [4][5][6][7][8] In human patients, PT is used as an aid to identifying allergens involved in persistent asthma, drug allergy, insect sting allergy, food allergy, seasonal allergic rhinitis and AD. 9,10 In humans, PT is thought to be a more rapid and less invasive test than IDT.…”
Section: Introductionmentioning
confidence: 99%